2020
DOI: 10.1177/1759091420922929
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging Detects Acute and Subacute Changes in Corpus Callosum in Blast-Induced Traumatic Brain Injury

Abstract: There is a critical need for understanding the progression of neuropathology in blast-induced traumatic brain injury using valid animal models to develop diagnostic approaches. In the present study, we used diffusion imaging and magnetic resonance (MR) morphometry to characterize axonal injury in white matter structures of the rat brain following a blast applied via blast tube to one side of the brain. Diffusion tensor imaging was performed on acute and subacute phases of pathology from which fractional anisot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
(86 reference statements)
0
8
0
Order By: Relevance
“…DTI measurements also tend to be exacerbate with time post-injury: we have reported an increase in the volume of microstructural damage between post-injury day 4 and 30 13 , and Badea et al have reported greater changes in DTI at 90 days relative to 7 days post-injury 61 . Another study found region-specific changes in DTI between 1 and 14 days after injury, reflecting regional differences in time to vasogenic or cytotoxic edema and demyelination 62 . In the present study, we did not observe a significant effect of rbTBI on FA in the prefrontal cortex or nucleus accumbens, but we did observe a significant interaction between rbTBI and oxycodone self-administration in the nucleus accumbens.…”
Section: Discussionmentioning
confidence: 96%
“…DTI measurements also tend to be exacerbate with time post-injury: we have reported an increase in the volume of microstructural damage between post-injury day 4 and 30 13 , and Badea et al have reported greater changes in DTI at 90 days relative to 7 days post-injury 61 . Another study found region-specific changes in DTI between 1 and 14 days after injury, reflecting regional differences in time to vasogenic or cytotoxic edema and demyelination 62 . In the present study, we did not observe a significant effect of rbTBI on FA in the prefrontal cortex or nucleus accumbens, but we did observe a significant interaction between rbTBI and oxycodone self-administration in the nucleus accumbens.…”
Section: Discussionmentioning
confidence: 96%
“…This pattern is thought to be the MR representation of a trauma-induced disturbance in the microstructure of the axonal tissue [ 36 ]. Furthermore, certain local brain regions, including the frontal lobes, the corpus callosum, the centrum semiovale, and the internal capsule, may be more susceptible to these changes after TBI than others [ 42 , 44 , 45 , 46 , 47 , 48 ]. Although detecting these changes may be helpful in the diagnosis of CT-negative mild TBI, it is less clinically relevant for those in whom TBI has already been confirmed.…”
Section: Diffusion Tensor Imaging (Dti)mentioning
confidence: 99%
“…Even though the acute symptoms of mTBI may be mild and transient, experimental and clinical studies have found metabolic, biochemical, and structural changes caused by mTBI. Mild TBI causes a complex pathophysiological cascade, including dramatic alterations in ionic homeostasis ( Katayama et al, 1991 ), disruption of the blood–brain barrier (BBB) ( Walls et al, 2016 ; Kuriakose et al, 2018 ), injury-induced neuroinflammation ( Kokiko-Cochran and Godbout, 2018 ; Missault et al, 2019 ), and diffuse axonal injury ( Ling et al, 2012 ; Venkatasubramanian et al, 2020 ). However, majority of mTBI patients experience neurological dysfunction with no findings on conventional clinical imaging methods, such as structural magnetic resonance imaging (MRI) or computed tomography (CT) ( Le and Gean, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several advanced in vivo imaging techniques have been used to investigate TBI to better understand the temporal microstructural and functional changes following TBI, such as diffusion tensor imaging (DTI), functional MRI (fMRI), MR spectroscopy (MRS), positron emission tomography (PET), etc. ( Croall et al, 2014 ; Zhuo et al, 2015 ; Harris et al, 2016 ; Jaiswal et al, 2019 ; Kulkarni et al, 2019 ; Venkatasubramanian et al, 2020 ). DTI has been widely used to investigate the microstructural responses after mTBI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation